The Result of Functional Mobility Scale (FMS) on Cerebral Palsy Spastic Diplegic that treated by SEMLS (Single Event Multi Level Surgey) method in Orthopaedic Hospital Prof. Dr. R. Soeharso, Surakarta - Hadinoto, Seti Aji; Satriadi, Anung Budi; Wujoso, Hari (Indonesian Journal of Medicine, 2017)
Background: Cerebral Palsy is a permanent non-progressive brain disorders that occur in early childhood where abnormalities in the brain due to damage on immature brain can cause movement disorders and postural dysfunctionNowadays, the treatment of choice for CP Spastic diplegic is using SEMLS (Single Event Multi Level Surgery). There was many scoring to evaluate outcome of SEMLS, but only a few scoring system that can evaluate changing after SEMLS. Functional Mobility Scale (FMS) is an outcome measure designed to evaluate mobility of children with cerebral palsy (CP). FMS has been shown to detect both improvement and deterioration in mobility status during the rehabilitation period following multilevel orthopaedic surgery in children with spastic diplegicSubjects and Method:This was a cross sectional observasional study. The sample are obtained by sensus from January 1st 2014 untill March 1st 2015. The patientÃ¢â¬â¢s characteristic that we include in this study are gender, age when the patient had a surgery, and where the contracture are involved. We evaluate the outcome using FMS before operation, 3 month, 6 month, 9 month, and 12 month after operation on three different distance (5, 50, 500 meter) that represent home, school, and community. After that we analyze the result using regression logistic model to better understands about changes and time of changes on patient after SEMLS procedure. We also analyze the corelation between age, sex, and location of contracture with the outcome after SEMLS procedureResult : 51 patients were reviewed and identified, there were 31 males (61%) and 20 females (39%), mean age when the patient was operated was 8.07 years old, with the most common cases are CP Spastic Diplegic with hip, knee, ankle contracture bilateral about 41 patient (80.3%), knee ankle bilateral about 7 patient (13.2%), and hip ankle bilateral about 3 patient (5.88%). From evaluation of FMS scoring, we found most patient had an improvement on their mobility after SEMLS procedure (OR > 1), with the time changes for 5 and 50 meters distance is at six months (OR : 1.52) and (OR= 1.47), and 500 meters is at 12 months (OR= 3.45). We also found no significant relationships (p value > 0.05) between age (p value= 0.632), sex (p value= 0.576) and location of contracture (p value= 0.222) with the outcome of the FMS after SEMLSConclusion: We found that SEMLS gives a good result to increased mobility of patient with CP Spastic Diplegic. FMS Score were able toÃÂ  asses the outcome of SEMLS procedure, and also responsive to change that occur after SEMLS. Age, sex, andÃÂ  contractureÃ¢â¬â¢s location were not significantly influence the FMS outcome after SEMLSKeywords: CP Spastic Diplegic, SEMLS (Single Event Muti Level Surgery), FMS (Functional Mobility Scale).Correspondence:ÃÂ Seti Aji Hadinoto. Masters Program of Family Medicine, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java.Indonesian Journal of Medicine (2017), 2(2): 100-106https://doi.org/10.26911/theijmed.2017.02.02.04ÃÂ